60 + 4. outros anos da mesma crise: histórias, imagens e outros diálogos - Silva, Paulo Sérgio (2013)
60+4. Other years of the same crisis. History, Images and other dialogues, this research interweaves history toa socio-political-cultural analysis of the civilian-military pre-coup in the sixties, retrieves and presents old and new characters, producers of multiple evidences entangled to that plot. The production of dialogues, which coexist and interpenetrating the international context of those years, pointed to the clash of political culture, manager of ceaseless quest for hegemony that characterized the period of bi-polarization between capitalist and communist. The reading of headlines and images that composed some of the front pages / covers of the newspapers Folha de S. Paulo and the Ultima Hora, between the years of 1960 and 1964; as well as consistent literature visitation about the subject, became exciting paths for socializing with partisan disputes; characters from politics and military scene; exciting cultural production, foreign interference, among others, reverberating as sounding that social place. The civic-military coup of 1964 composes memories from that and this lived present